MONITORAMENTO DE RESÍDUOS DE AGROTÓXICOS DA CLASSE DOS ORGANOFOSFORADOS POR CGDFC EM AMOSTRAS DE LEITE FLUÍDO E EM PÓ - Lucia Helena Pinto Bastos; Adherlene Vieira Gouvêa; Nina Daddário Ortiz; Maria Helena Wohlers Morelli Cardoso; Silvana do Couto Jacob; Armi Wanderley da Nóbrega (Química Nova, 2015)
Samples of whole fluid pasteurized, UHT and powdered milk were analyzed for the presence of organophosphorus pesticide residues (OPR) using the QuEChERS method with detection by GC-FPD and confirmation by UPLC-MS/MS. A total of 23% of fluid milk samples and 27% of powdered milk samples contained at least one organophosphorus residue. The OPR found in the samples showed these can reach the milk and remain even after pasteurization, sterilization and drying processes. Some domestic sanitary residues were also present in the powdered milk samples. These residues have no LMR in Brazilian food legislation and are therefore not taken into account in food intake evaluations. There was an unidentified chromatographic peak in 30% of all the liquid and powdered milk samples, indicating the presence of some other contaminant.